KAJIAN YURIDIS TENTANG PROBLEMATIKA OUTSOURCING PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 27/UUP-IX/2011 (Studi pada PT. PLN (PERSERO) Wilayah Maluku dan Maluku Utara) - Heillen M. Y. Tita (SASI, 2014)
Constitutional Court Decision Number 27 / UUP-IX / 2011 is the ruling Judge Constitutional Court on the judicial review of articles in Law Number 13 of 2003 on Labour as positive law for industrial relations in Indonesia. Practice of handing over part of its work to another company, known by the term outsourcing, is a means used by a company to be able to make profits and save large financing. By using normative juridical method, with casuistry approach that elevates examples of cases that occur in the PT. PLN (PERSERO) Region Maluku and North Maluku. This research study into a material that can contribute to the relevant parties.